Clinical Characteristics of Mother-Infant Dyad and Placental Pathology in COVID-19 Cases in Predominantly African American Population - Sanket Jani; Suzanne M Jacques; Faisal Qureshi; Girija Natarajan; Sujit Bajaj; Pradeep Velumula; Cindy Agu; Monika Bajaj (Thieme Medical Publishers, Inc., 2021)
Abstract Objective In this currently evolving coronavirus disease 2019 (COVID-19) pandemic, the evidence is scarce about the impact of COVID-19 infection on women in labor and neonates in an inner city African-Americans (AA) population. The objective of this study was to evaluate the clinical outcomes and placental pathology in mother-infant dyads in COVID-19 cases. Study Design Retrospective chart review was conducted on 34 COVID-19 positive mother-infant dyads to study their baseline characteristics and outcomes. Placental pathology was reviewed by two perinatal pathologists. Results COVID-19 was noted in 3% of pregnant women who delivered in our institution. The majority (82%) of them were asymptomatic. Out of the four mothers who were symptomatic, only three (9%) required supplemental oxygen. None of them required invasive ventilation. All the neonates tested negative for COVID-19 at 24 hours of age. There were no gross or microscopic pathological abnormalities detected that could be definitely associated with any COVID-19 related complications during pregnancy in any of the 34 placentas. Conclusion COVID-19 does not appear to increase morbidity and mortality among pregnant women and their neonates in a predominantly AA population. Our study did not find any evidence of vertical transmission of COVID-19 infection nor any specific findings on placental pathology. Key Points Majority of women infected by coronavirus disease 2019 (COVID-19) during labor were asymptomatic. None of the newborns tested positive for COVID-19 at 24 hours of age. Placental pathology findings were nonspecific in COVID-19 mothers.